New digital drilling process monitoring: Instrumentation, validation and calibration - Yanpeng Sun; Zuyu Chen; Fangcai Xu; Yufei Zhao; Ruilang Cao; Dong Li (Journal of Rock Mechanics and Geotechnical Engineering)
This study aims to enhance the digital drilling process monitoring (DPM) or monitoring while drilling (MWD) technique, which is a widely recognized method in geological exploration for evaluating rock mass quality. First, robust displacement and torque measurement facilities for rotary-core drilling are discussed. The conventional cable encoder for displacement measurement is replaced with a magnetostrictive displacement sensor, which is more reliable in harsh field drilling environments. This enables the measurement of the bit position with an accuracy of <1 mm. Most importantly, this new instrument is proven to be successful in improving the detection of structural discontinuities with thicknesses >1 mm. In addition, by measuring the electric current of the driving motor, the torque applied to the bit is conveniently and accurately converted. These innovations ensure high-quality data collection for DPM practices. Second, two indices derived from DPM are proposed to quantitatively describe rock mass quality. The specific energy index (SEI) and specific penetration index (SPI) are based on the principles of energy conservation and Mohr-Coulomb failure criterion, respectively. Extensive field tests conducted in a dam grouting area confirm a linear relationship between the thrust force and penetration per rotation, and between the torque and penetration per rotation. The correlation ratios of the related regressions are typically >0.9. These two indices allow for the quantitative interpretation of DPM data into rock mechanics characteristics, such as uniaxial compressive strength, rock quality designation (RQD), and rock mass permeability, eliminating the need for subjective judgment normally involved in the currently used rock mass quality rating approaches.